ANIMASI PEMBELAJARAN BANGUN RUANG UNTUK SEKOLAH DASAR KELAS IV BERBASIS ANDROID - Akbar Himawan Fariansyah; Laila Septiana (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
Development of interactive animation media for elementary students now is a medium that can be one of the other options in giving a lesson, which was once only use books and pictures berwarna. As in learning Geometric in elementary school which only use the book makes students bored and difficult to learn. This makes the child less concentration in capturing lessons given by teachers, therefore media-based interactive animation andorid learning can be one of the teachers in providing the material introduction Geometric. With so students will feel happy and more motivated to learn by using these learning media. The objective of this study media to help learning the subject of the introduction of Geometric developed by Adobe Flash Professional CS6 and Android Smartphones. In writing this paper, the author discusses the Geometric learning applications either conversation or other learning applied into an android Smartphone. This application combines learning and playing, and this is a solution that children do not get bored in terms of learning.